(untitled)
In this paper, the authors prove that the multilinear fractional integral operator T_Ω,α^A_1,A_2 and the relevant maximal operator M_Ω,α^A_1,A_2 with rough kernel are both bounded from L^p (1 < p < ∞) to L^q and from L^p to L^n/(n−α),∞ with power weight, respectively, whereT_Ω,α^A_1,A_2(f)(x) =_R^nR_m_1(A_1;x,y)R_m_2(A_2;x,y)|x-y|^n-α+m_1+m_2-2 Ω(x-y)f(y)dyandM_Ω,α^A_1,A_2(f)(x)= _r > 01r^n−α+m_1+m_2−2 _|x−y|, number=3, journal=Analysis in Theory and Applications, year=2012, month=Oct., pages=224–231